(untitled) (Global Journal of Management and Business Research, 2020)
This research raises the question of budgetary determination of the price level in a context where the Central Bank seeks to stabilize prices and governments record increasing levels of public debt and public deficit. This is particularly about studying the effects of public debt and the public deficit on inflation. Using data from 39 countries in sub-Saharan Africa covering the period from 1982 to 2017, we tested budget theory of price levels. The results of econometric estimates obtained by GMM methods show that the budget deficit and the public debt associated with it have positive and significant effects on inflation in sub-Saharan Africa.